Autonomous vehicles between anticipation and apprehension: Investigations through safety and security perceptions. (September 2021) - Hussain, Qinaat; Alhajyaseen, Wael K.M.; Adnan, Muhammad; Almallah, Mustafa; Almukdad, Abdulkarim; Alqaradawi, Mohammed
Abstract: Due to the ongoing enormous infrastructural developments and car ownership culture in Qatar, it could be one of those countries to introduce Autonomous Vehicles (AV) technology at the early stages. Therefore, this study surveyed a number of residents at the State of Qatar to improve our understandings of their perceptions regarding overall safety of AV (General_safety), safety due to the fact that AV could eliminate human errors (Human_errors), safety due to the interactions between Human-Driven Vehicles (HDV) and AV (HDV-AV_interactions), performance in harsh environmental conditions, security, comfort level, travel time, congestion and operational costs. In addition, the study uncovered the relationships of public perceptions towards AV and some other contextual factors with the willingness to adopt it in the future. To study these relations, we relied on a Structural Equation Modeling. Overall, the results showed that respondents had higher and positive perceptions regarding "General_safety" and "Human_errors", however, they were more concerned about "HDV-AV_interactions" and its security. In addition, individuals' preference to shift to AV in the future was positively correlated with their perception level of "General_safety", "Human_errors", Comfort and Travel_time. Regarding ethnicity of the respondents, non-Arabs reported higher concerns regarding AV security, compared to Arabs. Furthermore, interestingly the results revealed that individuals having higher knowledge about AV technology had more concerns on "General_safety" and "HDV-AV_interactions", while they had positive perceptions that AV could eliminate human errors. The findings from this study are anticipated to allow AV manufacturers and other relevant authorities to enhance public confidence towards AV technology by targeting different sub-groups through particular safety or security awareness campaigns. Highlights: Demographic characteristics were found to affect public perceptions about AV. Higher concerns were reported for AV safety in mixed traffic conditions and its security. Willingness to use AV was positively correlated with perception level of AV's safety. Perceived comfort level significantly affected individuals' preference to shift to AV.